Edukasi Pentingnya Vaksin Covid-19 Di Masa Pandemi Pada Masyarakat di Kelurahan Baruga dan Watubangga Kota Kendari - La Ode Muhamad Sety; Hariati Lestari; Putu Eka Meiyana Erawan (PT.Mantaya Idea Batara, 2021)
Covid-19 is still a public health problem in the world, causing more than five million deaths. Indonesia is one of the countries that has quite a large number of Covid-19 cases, namely more than four million confirmed cases with one hundred and four thousand deaths. One of the efforts that have been made by the government in the context of preventing and controlling the disease is vaccination. However, even though the program is very good, not all people have accepted the COVID-19 vaccination program. This situation was also experienced at partner locations where in the preliminary survey, the results obtained were that public knowledge and awareness of the COVID-19 vaccine was still low. The participants were 50 posyandu cadres consisting of 25 people from Baruga Village and 25 people from Watubangga. The dedication method used is a lecture that begins with a pre-test, then counseling is carried out and ends with an evaluation using a post-test. The results of the evaluation showed an increase in knowledge after education about the benefits of the COVID-19 vaccine was carried out. The community and the head of the village agreed to help the government increase the coverage of the vaccine, which will start from the posyandu they have fostered.